Cardio-oncology care in Africa: current trends and disparities - Princess Afia Nkrumah-Boateng; Adam Ben-Jaafar; Allswell Naa Adjeley Boye; Pearl Ohenewaa Tenkorang; Toufik Abdul-Rahman; Wireko Andrew Awuah (Cardio-Oncology)
Abstract The emerging discipline of cardio-oncology addresses the cardiovascular complications associated with cancer therapies. In sub-Saharan Africa (SSA), where both cardiovascular disease (CVD) and cancer-related mortality are increasing, the development of cardio-oncology services remains limited. This correspondence assesses the current state of cardio-oncology in Africa, highlighting significant gaps in infrastructure, workforce, and policy. Despite the establishment of a single accredited cardio-oncology unit in South Africa, formalized services are lacking in the majority of African countries, leading to fragmented care and increased incidence of treatment-related cardiotoxicity. Key barriers include inadequate specialist training, limited diagnostic resources and a lack of standardized care protocols. The paper outlines strategic interventions, including multidisciplinary training, integration of cardiovascular screening into oncology, research funding, and policy reform. Strengthening cardio-oncology services is essential to reduce the dual burden of cancer and CVD and improve clinical outcomes for affected populations in SSA.